Nutrients measurements from METEOR cruise M76/2 in the Benguela Upwelling System off Namibia in May 2008 - Kay-Christian Emeis (PANGAEA, 2025)
Water samples were taken with a conductivity-temperature-depth (CTD)/rosette sampler and were filtered over precombusted GF/F Filters onboard. Filtrates were stored frozen in acid-washed polypropylene bottles for nutrient and nitrate isotope analysis. Nutrient concentrations of samples were measured with a Bran & Luebbe SCALAR autoanalyzer in the home laboratory in Hamburg applying standard methods. The method for stable isotope composition of nitrate is described in Nagel et al., 2013.